2013
DOI: 10.1039/c2ta01312f
|View full text |Cite
|
Sign up to set email alerts
|

Layered titanate nanostructures and their derivatives as negative electrode materials for lithium-ion batteries

Abstract: Ti-based materials have been intensively investigated and considered as good potential negative electrode materials for lithium-ion batteries (LIBs) due to their high safety, superior rate capability and excellent cyclic stability. This feature article summarizes the recent progress of a new class of layered titanate (H 2 Ti n O 2n+1 $H 2 O) nanostructures and their derivatives, including TiO 2 polymorphs, novel titanate nanostructures of Zn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 74 publications
(92 reference statements)
0
51
1
Order By: Relevance
“…Chen et al synthesized Ti 3þ doped TiO 2 via a solvothermal batch method and suggested that the Ti 3þ increased electronic conductivity, resulting in an improved rate performance with a capacity of 81 mAh g À1 at an applied current of 3 A g À1 [39]. Recently, it has been reported that rutile TiO 2 can exhibit good rate capability [32,40]. Hong et al investigated self-assembled nanoporous rutile TiO 2 mesocrystals, which retained a capacity of 77 mAh g À1 at an applied current of 3.4 A g À1 [41].…”
Section: Resultsmentioning
confidence: 98%
“…Chen et al synthesized Ti 3þ doped TiO 2 via a solvothermal batch method and suggested that the Ti 3þ increased electronic conductivity, resulting in an improved rate performance with a capacity of 81 mAh g À1 at an applied current of 3 A g À1 [39]. Recently, it has been reported that rutile TiO 2 can exhibit good rate capability [32,40]. Hong et al investigated self-assembled nanoporous rutile TiO 2 mesocrystals, which retained a capacity of 77 mAh g À1 at an applied current of 3.4 A g À1 [41].…”
Section: Resultsmentioning
confidence: 98%
“…4,6,7 Titanium dioxide materials have attracted increasing attention as promising LIB anode materials for replacing conventional graphite anodes owing to their superior features such as safety improvement, low cost, cycling stability, and satisfactory chemical and thermal stabilities. 3,[7][8][9][10][11][12][13][14] Particularly, TiO 2 exhibits very small volume expansion (<4%) and, more importantly, operates at a relatively high working voltage (1.7 V vs. Li/Li + ) during Li + insertion/extraction, which eliminates the influence of the solid electrolyte interface layer and avoids the risk of lithium electrodeposition from electrolytes in LIBs, thus further ensuring the cycling stability and safety of batteries. However, the poor Li ion diffusivity and low electronic conductivity of TiO 2 materials (10 −11 -10 −12 −1 m −1 ) limit the reversible capacity and fast charge/discharge rate for practical applications in high-power LIBs.…”
mentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) based on TiO 2 anodesh ave been widely investigated in recent decades due to the intrinsica dvantages of TiO 2 of low cost, good cycling performance, and high safety. [1,2] Among the variousp olymorphs of TiO 2 ,a natase, [3][4][5][6][7][8] bronze, [9][10][11][12][13][14][15][16] and rutile [17,18] are the most three common forms and have been considereda sm ost suitable candidates for active electrode materials in LIBs. The rutile phase is generally regarded as the most thermodynamically stable structure.…”
Section: Introductionmentioning
confidence: 99%